2009
DOI: 10.1002/jso.21258
|View full text |Cite
|
Sign up to set email alerts
|

Nadir CA‐125 level is an independent prognostic factor in advanced epithelial ovarian cancer

Abstract: The prognostic role of the nadir CA-125 is independent of residual tumor size in the patients with advanced EOC. However, it is still unclear whether maximal surgical effort can affect the nadir CA-125 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Patients whose nadir CA-125 value was below 10 U/ml had longer median OS than those patients whose nadir was 11 U/ml, although neither HRs nor p-values were presented in the original paper. Following this, other groups have subsequently validated the concept that the CA-125 nadir after primary treatment of EOC may serve as a prognostic factor for PFS and OS, even though the patient population and the clinical setting differ notably amongst studies [34][35][36][37] (Table 2). Van Altena et al have recently reported the largest study (n=331) evaluating the CA-125 nadir after primary treatment and its potential association with both PFS and OS [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients whose nadir CA-125 value was below 10 U/ml had longer median OS than those patients whose nadir was 11 U/ml, although neither HRs nor p-values were presented in the original paper. Following this, other groups have subsequently validated the concept that the CA-125 nadir after primary treatment of EOC may serve as a prognostic factor for PFS and OS, even though the patient population and the clinical setting differ notably amongst studies [34][35][36][37] (Table 2). Van Altena et al have recently reported the largest study (n=331) evaluating the CA-125 nadir after primary treatment and its potential association with both PFS and OS [38].…”
Section: Resultsmentioning
confidence: 99%
“…This association seems particularly signifi cant in those patients who have optimal debulking [44]. In addition, the lowest CA-125 value (CA-125 nadir) achieved after the primary treatment of EOC has consistently been associated with survival (PFS) outcome [33][34][35][36][37][38]. Again, if this observation could be validated by using prospective data sets from large phase III clinical trials, it may be worth further investigating if the CA-125 nadir levels could serve to stratify patients into different subgroups when designing future clinical trials in the adjuvant setting, especially from the perspective of maintenance or consolidation therapy strategies [45] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most famous biomarker in EOC is CA-125, which has been used in both diagnosis of the disease and monitoring of treatment [4-6]. Recent evidence indicates that the nadir CA-125 level after completion of primary treatment was associated with prognosis [7-11]. Though the use of prognostic information is not well studied, some have proposed its possible role in the stratification of patients in clinical trials and planning further treatment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have usually used the cut-off value of 10 and/or 20 U/mL [7,9-11]. Some suggested 12 U/mL as a cut-off value based on the median CA-125 level of their study cohort [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of studies have indicated that a nadir CA-125 level above 10 U/ml is an independent prognostic factor associated with progression-free survival (PFS) in patients who achieved complete remission (CR) after first-line treatment [5,6,7,8,9,10]. In addition, a study suggested that not only the nadir level, but also the level after six cycles of standard chemotherapy was an independent prognostic factor [11].…”
Section: Introductionmentioning
confidence: 99%